Ammonia Mitigation Practices in A Closed-House Broiler Farm in An Agrocomplex System: A Case Study from Moncongloe Bulu, Indonesia - Tampi, Syalomita Y.; Tangkere, Evacuree S.; Tangkau, Linda M.S.; Rumondor, Delly B.J.; Kumajas, Nontje; Sompie, Florencia N. (Jurnal Agroekoteknologi Terapan, 2026)
Ammonia accumulation is one of the main air-quality challenges in intensive broiler production, particularly in closed-house systems where large numbers of birds are reared under controlled environmental conditions. This study aimed to analyze the practices used to reduce ammonia (NH3) concentration in the closed-house broiler facility of CH Kembar Farm, Moncongloe Bulu, Indonesia. The study was conducted from September to November 2024 using a descriptive mixed-method approach. Data were collected through direct field observation, interviews with farm management, and NH3 measurement using an ammonia kit test (Hydrion AM-40). The findings showed that ammonia control at the farm was supported by routine maintenance of key housing equipment, including exhaust fans, blower fans, cooling pads, and backup electrical systems, as well as by regular litter management through EM-4 application and litter stirring three times per week until harvest. The measured NH3 concentration was consistently reported as 10 ppm at all observation points, indicating that the in-house ammonia condition remained below the threshold value cited in the source manuscript. These results suggest that effective ammonia mitigation in closed-house broiler production depends not only on housing technology, but also on the consistency of daily operational management. Overall, this study provides practical field-based evidence that integrated environmental-control and litter-management practices can support acceptable air-quality conditions in commercial broiler production under tropical conditions. Keywords: air quality; ammonia concentration; broiler chickens; closed-house system; litter management